Making global health 'work': Frontline workers' labour in research and interventions. Issue 12 (2nd December 2022) - Kingori, Patricia; Kombe, Francis; Fehr, Alexandra
ABSTRACT: This Special Issue of Global Public Health draws on the concept of 'body work' among those employed to support operationalising, researching, and implementing global health while in direct contact with the bodies of others. This collection brings into sharp focus the specific forms of labour of those occupying positions as frontline workers - those who make global health work. Making Global Health Work includes authors from diverse backgrounds, disciplines, and geographies. Through compelling ethnographies, qualitative interviews, and focus group discussions, they explore 'body work' globally, including: Afghanistan, Bangladesh, Ethiopia, India, Indonesia, Kenya, Malawi, Myanmar, Nigeria, Nepal, Pakistan, Sierra Leone, South Sudan, Tanzania, Thailand, The Democratic Republic of the Congo (DRC), The Gambia, Vietnam, and Zimbabwe. These papers demonstrate that proximity to, and work on, the bodies of others engenders specific forms of (physical, emotional, mental, social, ethical, and political) labour, which occur not only in emergencies and pandemics, but also throughout the quotidian practice of global health. Making Global Health Work provides insights into the provision of maternal healthcare, treatment of multidrug resistant tuberculosis, rapid HIV testing programmes, sleeping sickness and polio eradication campaigns, mass drug administration clinical trials, epidemic preparedness and response, and the management and care of dead bodies. These papers argue for greater attention by global health actors on frontline workers in management of the complexities involved in making global health work .